(untitled) (Research, Society and Development, 2021)
This retrospective observational cross-sectional study aimed to analyze the distribution of visceral leishmaniasis (VL) cases in Três Lagoas registered between January 2007 and August 2021, through data processed by the Epidemiological Surveillance Service based on the notification of the National System of Diseases and Notifications. In this period, 231 cases were confirmed, being 137 male (59.3%) and 94 female (40.7%). Was observed a higher prevalence of cases between ages 0-4 years (30.8%), 20-39 (22.5%) and 40-59 (19.9%). Also was observed a higher percentage of infected Caucasian individuals (45.4%) and individuals with low education: elementary school II (22.1%). The most prevalent clinical manifestations were fever (85.3%), splenomegaly (76.6%), weakness (67.1%), weight loss (65.8%) and hepatomegaly (62.8%). It was found that 80.1% of patients received pharmacological treatment, mainly using pentavalent antimonials (56.7%), and that 26 patients (11.3%) died during the period due to complications caused by VL. The spatial analysis showed a homogeneous distribution of VL cases in the city’s urban perimeter without predominant regions. Finally, it was observed that the incidence and mortality by VL has been decreasing in recent years, however maintaining high rates of lethality and transmissibility, placing the municipality in the third with the highest transmission rate in the state. In view of these aspects, we conclude that VL is still a serious public health problem in the city and that despite the slight drop in incidence and mortality rates, it still presents values higher than the national average and high dissemination of the disease in the urban area.